Sales Growth - Baumgartner, Thomas; Hatami, Homayoun; Valdivieso, Maria (Ascent Audio, 2019)
The challenges facing today's sales executives and their organizations continue to grow, but so do the expectations that they will find ways to overcome them and drive consistent sales growth. There are no simple solutions to this situation, but in this thoroughly updated second edition of Sales Growth, experts from McKinsey & Company build on their practical blueprint for achieving this goal and explore what world-class sales executives are doing right now to find growth and capture it-as well as how they are creating the capabilities to keep growing in the future. Based on discussions with more than 200 of today's most successful global sales leaders from a wide array of organizations and industries, Sales Growth puts the experiences of these professionals in perspective and offers real-life examples of how they've overcome the challenges encountered in the quest for growth. Engaging and informative, this timely book details proven approaches to tangible top-line growth and an improved bottom line. Created specifically for sales executives, it will put you in a better position to drive sales growth in today's competitive market.